Photo-response in CuPbBr3 - Bharti P.C.; Jha P.K.; Jha P.A.; Singh P. (My University, 2025)
The perovskite halides have attracted the Solar cell researchers' community as an active material for the solar cells. Copper lead bromide (CuPbBr3) is one of the inorganic perovskite materials known as light absorbing materials with band gap of ∼2.87 eV. In the present work, CuPbBr3 is synthesized through cold sintering technique in ambient atmosphere. The X-ray diffractograms revealed the single phase formation with cubic phase which is also verified through reported results. The material shows good photo response in 1.5AM-G solar light. © 2019 Elsevier Ltd.